ChemInform Abstract: Assembly of Functionalized Carbocycles or N‐Heterocycles Through a Domino Electrocyclization—[1, 2] Migration Reaction Sequence. Issue 46 (November 2015) - Jana, Navendu; Driver, Tom G.
Abstract Review: 114 refs.